Master of TESOL students’ conceptions of assessment: questioning beliefs - Martínez Marín, Juan Diego (Universidad de Costa Rica, 2021)
The current descriptive study investigates the conceptions of a group students (pre-service and in-service teachers) enrolled in a Master of TESOL (Teaching English to Speakers of Other Languages) at La Trobe University, Australia, have of assessment in the context of English language teaching. This study was conducted in first place to address a gap in the literature about English teachers’ conceptions of assessment, and I second place to explore the level of agreement among those conceptions and the type of assessment preferred by the participants. For this purpose, 26 active students in the course accepted the invitation to participate in the study and completed an online survey administered through Qualtrics Management Platform. This quantitative descriptive study done in 2020 used Survey as the research method since it promotes the collection of data to describe the research object. The quantitative data obtained through an online survey were summarized and graphed in tables with the objective of answering the research questions. The results showed that participants’ understandings of assessment and forms of assessment were slightly inclined towards the use of summative assessment rather than formative. In contrast, their conceptions of assessment purposes and principles were inclined towards formative assessment features. All in all, it could be said that even though these participants seemed to cope more with summative assessment, they favoured formative purposes and principles of assessment. This suggests that respondents’ summative views of assessment in the use of types and forms of assessment are potentially affected by institutional demands, and do not entirely reflect the respondents’ assessment understandings.